Answer: point form (-1,-2)
Equation form x=-1 y=-2
Step-by-step explanation:
Answer:
<em>x </em>= -5
Step-by-step explanation:
You have to work backwards.
53 + 7 = 60
60 ÷ 12 = 5
Add the negative »»» -5
Answer:
8x²- x -8
Step-by-step explanation:
The question is not well written. I guess what you mean is:
Subtract -2x^2+4x-1 ( minus 2x squared plus 4x minus 1) from 6x^2+3x-9 (6x squared plus 3x minus 9).
To subtract -2x^2+4x-1 from 6x^2+3x-9, that is
6x^2+3x-9 - (-2x^2+4x-1). This can be written as
6x²+3x-9 - (-2x²+4x-1)
Now, opening the bracket, we will get
6x²+3x-9 +2x²-4x+1
Then, collecting like terms, we get
6x²+2x²+3x-4x-9+1
6x²+2x² = 8x²
3x-4x = -x
-9+1 = -8
∴6x²+2x²+3x-4x-9+1 becomes
8x²-x -8
The answer is 8x²-x -8.
Answer:
z = -1
Step-by-step explanation:
add like terms: 13z = -13
divide both sides by 13: z = -1